ANALYZING THE PRELUDES AND DETERMINANTS OF ARTIFICIAL INTELLIGENCE AND LEARNING IN THE 21st CENTURY: A CRITICAL ANALYSIS - Sonal Sisodia; Sarvesh Raj Rocque (International Journal of Innovative Technologies in Social Science, 2022)
In the coming years, there will be a transformation of learning systems around the globe, which will be aided by new technologies and information science. With the advent of artificial intelligence and mobile devices with cutting-edge capabilities, the learning process will undergo the most significant changes in over a century. The use of mobile learning methods is becoming increasingly popular as new technology advances. According to the authors’ literature review, as the field of research advances, more and more researchers are investigating the effects of artificial intelligence on learning, teaching methods, and teacher evaluations. The paper also discusses the benefits of using artificial intelligence to facilitate independent learning. Rather than being seen as an adjunct to learning and teaching, Artificial Intelligence helps to enable a fundamental shift in thinking about what should be taught and how it should be taught. It is both an exciting opportunity and a serious responsibility for a company that are of big size. Toward meeting this challenge, this article examines several key precursors and determinants of learning and artificial intelligence. Recently, a number of terms have been introduced into the field of learning, including portal connectivity, artificial intelligence, big data, machine learning, mobile technologies, and intelligent learning patterns. Due to these changes, society and education have undergone unprecedented transformations. The authors of the study conclude that the use of artificial intelligence in learning is likely to follow the trend that shows a rapid increase after a period of relative stability. As artificial intelligence develops rapidly in the field of learning, the way knowledge is conveyed and the ability to learn new things will be greatly altered.